An open label, non-randomised, phase IIIb study of trametinib in combination with dabrafenib in patients with unresectable (stage III) or distant metastatic (stage IV) BRAF V600-mutant melanoma: A subgroup analysis of patients with brain metastases. (November 2022) - Dutriaux, Caroline; Robert, Caroline; Grob, Jean-Jacques; Mortier, Laurent; Dereure, Olivier; Lebbe, Céleste; Mansard, Sandrine; Grange, Florent; Neidhardt, Eve-Marie; Lesimple, Thierry; Machet, Laurent; Bedane, Christophe; et al.
Abstract: Background: Despite the poor prognosis associated with melanoma brain metastases (BM), data concerning these patients and their inclusion in clinical trials remains scarce. We report here the efficacy results of a subgroup analysis in patients with BRAFV600-mutant melanoma and BM treated with BRAF and MEK inhibitors dabrafenib (D) and trametinib (T). Patients and methods: This phase IIIb single-arm, open-label, multicenter, French study included patients with unresectable stage IIIc or IV BRAFV600-mutant melanoma with or without BM. The present analysis focuses on patients with BM. Response rates were determined clinically and/or radiologically as per standard clinical practice. Progression-free survival (PFS) was estimated using the Kaplan Meier analysis and modelled with multivariate Cox regression model. Risk subgroups were identified using an exponential regression tree analysis. Significance was set at p < 0.05. Results: Between March 2015 and November 2016, 856 patients were included and 275 (32%) patients had BM. Median PFS was 5.68 months (95% confidence interval [CI], 5.29–6.87). Significant independent factors associated with shorter PFS were ECOG ≥1, elevated serum lactate dehydrogenase (LDH), ≥3 metastatic sites, and non-naïve status. The binary-split classification and regression tree modelling identified baseline LDH and ECOG status as major prognostic factors. Conclusion: This is to date the largest, close to real-world, study in advanced BRAFV600-mutant melanoma patients with BM treated with D+T. ECOG >1, ≥3 metastatic sites and elevated LDH were associated with shorter PFS, a finding previously demonstrated only in patients without BM. Further studies are warranted to determine the optimal treatment sequence in this population. Highlights: This is the largest cohort of patients with BRAF V600-mutant melanoma and with brain metastases. The results confirm the clinical activity of trametinib + dabrafenib in these patients. LDH, Eastern Cooperative Oncology Group, number of metastatic sites and naïve/non-naïve status were associated with progression-free survival.